(untitled) (Basel Institute on Governance Policy Briefs, 2017)
This Policy Brief summarises the main findings and lessons learned from a research on corruption, social norms and behaviours in Rwanda. The findings show that, although Rwanda has successfully curbed corruption, favouritism continues to be used to secure preferential access to public health services. While the Rwandan experience illustrates how behavioural insights can effectively complement conventional anti-corruption approaches, further entry areas for deepening behavioural anti-corruption interventions are also identified.